MODEL SISTEM PENGAJUAN CUTI DENGAN METODE PROTOTYPE - Ramadhani, Silvia; Dewi, Mutiara Sintia; Rajani, Attila; Armansyah, Armansyah (UNIVERSITAS STEKOM, 2025)
Today's governments and organizations increasingly rely on information technology to increase productivity and efficiency. One important aspect of human resource management is the management of employee compensation and benefits. This article discusses the development of a web-based information system for human resource management and employee training. Prototypes are used in software development to provide silent communication between developers and system users. This information system makes it easier for employees to handle leave or permission at work without having to enter personal data and provides support to the team to meet goals.